HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEPATUHAN DIET DIABETES MELLITUS TIPE II DI RT 02 KAMPUNG TENUN SAMARINDA - Jahratul Mahya; Dian Ardyanti, Bernadetha (CV. ADIBA AISHA AMIRA, 2026)
Introduction: Diabetes Mellitus is a non-communicable disease that is one of the chronic diseases caused by insufficient insulin production by the pancreas that cannot be used effectively by the body. According to WHO 2020, there are 422 million people with Diabetes Mellitus in the world, while the prevalence in Indonesia reaches 10.6% of the total population of 179.2 million. East Kalimantan Province has a prevalence of Diabetes Mellitus of 2.26% and Samarinda city has a prevalence of 3.04%. Objective: This study was to determine the relationship between knowledge and attitudes with dietary compliance of Type II Diabetes Mellitus in RT 02 Kampung Tenun Samarinda. Methods: This study used quantitative research with an analytic design with a cross-sectional approach. The population in this study were all patients with Type II Diabetes Mellitus in RT 02 Kampung Tenun Samarinda as many as 35 respondents. The sample used is from the calculation of the Total Sampling technique, which is 35 respondents. Data analysis used in the variables of knowledge, attitude and compliance is the Gamma test. Results: The results of the Gamma test show that there is a relationship between knowledge and Type II Diabetes Mellitus diet compliance with a p-value = 0.003 (<0.005) which means there is a significant relationship. While the results of the relationship between attitude and Type II Diabetes Mellitus diet compliance get a p-value = 0.010 (<0.005) which means there is a significant relationship between attitude and Type II Diabetes Mellitus diet compliance in RT 02 Kampung Tenun Samarinda. Conclusion: There is a relationship between knowledge and attitude with dietary compliance of Type II Diabetes Mellitus in RT 02 Kampung Tenun Samarinda. Suggestion: It is hoped to increase knowledge and attitudes about Type II Diabetes Mellitus diet compliance by adjusting eating patterns to manage blood sugar levels in the body and prevent complications from Type II Diabetes Mellitus.